(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
This article discusses the traditional communication in Malay manuscript authorship based on the Hikayat Pelanduk Jenaka (Cod. Or. 1932). The process of traditional communication was analysed using content analysis methods and qualitative research techniques based on the R.Lina model: Two-way Planned Communication (RL: KDHT) (2013). The current analysis demonstrates the uniqueness of traditional communication in the authorship of Malay traditional manuscript in terms of the relationship between its author and God, individuality, society and nature. This article argues that the traditional Malay manuscript is able to generate a message that is entertaining and informative for readers. Makalah ini memfokus kepada komunikasi tradisi dalam kepengarangan manuskrip Melayu tradisional menerusi Hikayat Pelanduk Jenaka (Cod. Or. 1932). Bagi menggambarkan proses komunikasi tradisi, penulis menggunakan kaedah analisis kandungan serta teknik kualitatif menerusi model R.Lina: Komunikasi Dua Hala Terancang (RL: KDHT) (2013). Analisis kajian ini menunjukkan keunikan komunikasi tradisi dalam kepengarangan manuskrip Melayu tradisional, dan sorotan kepada elemen hubungan pengarang dengan Tuhan, individu, masyarakat dan alam. Makalah ini membahaskan tentang manuskrip Melayu tradisional yang dihasilkan oleh penulisnya yang berupaya menghasilkan mesej sehingga menghiburkan dan membawa maklumat kepada khalayak pembaca.